Classification system of the sagittal standing alignment in young adolescent girls - Dolphens, Mieke; Cagnie, Barbara; Coorevits, Pascal; Vleeming, Andry; Vanderstraeten, Guy; Danneels, Lieven (European spine journal, 2014)
Purpose The purpose of this cohort study was to classify sagittal standing alignment of pre-peak height velocity (pre-PHV) girls, and to evaluate whether identified subgroups were associated with measures of spinal pain. This study further aimed at drawing attention to similarities and differences between the current postural classification and a previous system determined among pre-PHV boys. Methods 557 pre-PHV girls [mean age, 10.6 years (SD, 0.47 years)] participated in the study. Three gross body segment orientation parameters and five specific lumbopelvic characteristics were quantified during habitual standing. Postural subgroups were determined by cluster analysis. Logistic regression was applied to assess the relationship between postural subgroups and spinal pain measures (pain and seeking care, assessed by self-administered questionnaire). Chi-square statistics, independent samples T test, and distribution-based methods were used for comparison with postural categorization in pre-PHV boys. Results and conclusion Among pre-PHV girls, clinically meaningful posture clusters emerged both on the gross body segment and specific lumbopelvic level. The postural subtypes identified among pre-PHV girls closely corresponded to those previously described in pre-PHV boys, thereby allowing the use of the same, working nomenclature. In contrast to previous findings among pre-PHV boys, no associations between posture clusters and spinal pain measures were significant in girls at pre-PHV age. When comparing discrete ‘global’ alignment scores across corresponding posture types, some intriguing differences were found between genders which might involve different biomechanical loading patterns. Whether habitual posture forms a risk factor for developing spinal pain up to adulthood needs evaluation in prospective multifactorial follow-up research.